Factors Predicting Difficult Biliary Cannulation during Endoscopic Retrograde Cholangiopancreatography for Common Bile Duct Stones - Hirokazu Saito; Yoshihiro Kadono; Takashi Shono; Kentaro Kamikawa; Atsushi Urata; Jiro Nasu; Haruo Imamura; Ikuo Matsushita; Tatsuyuki Kakuma; Shuji Tada (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims Difficult biliary cannulation is an important risk factor for post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP). Therefore, this study aimed to identify the factors that predict difficult cannulation for common bile duct stones (CBDS) to reduce the risk for PEP. Methods This multicenter retrospective study included 1,406 consecutive patients with native papillae who underwent ERCP for CBDS. Factors predicting difficult cannulation for CBDS were identified using univariate and multivariate analyses. Results Univariate analysis showed that six factors significantly predicted difficult cannulation: ERCP performed by non-expert endoscopists, low-volume center, absence of acute cholangitis, normal serum bilirubin, intradiverticular papilla, and type of major duodenal papilla. Multivariate analysis identified ERCP performed by non-expert endoscopists (odds ratio [OR], 2.5; p<0.001), low-volume center (OR, 1.6; p<0.001), intradiverticular papilla (OR, 1.3; p=0.007), normal serum bilirubin (OR, 1.3; p=0.038), and absence of acute cholangitis (OR, 1.3; p=0.049) as factors significantly predicting difficult cannulation for CBDS. Conclusions Initial cannulation by an experienced endoscopist, early rescue cannulation, or early takeover by an experienced endoscopist should be considered when performing ERCP for CBDS in the presence of factors predicting difficult cannulation.